Calcium and Bone Disorders in Pregnancy and Post-Partum Assessed through Radiological Imaging - Kailash Kumar Daseja, Kaneez Fatima, Akhtar Hussain Phul, Naimatullah Bozdar, Jia Dodani, Shahzeb (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the calcium and bone disorders in pregnancy assessed through radiological imaging. Study design: Prospective study. Place and duration of study: Department of Radiology, Chandka Medical College Hospital, Larkana from 1st July 2022 to 31st December 2022 Methodology: One hundred pregnant women were enrolled. The blood calcium levels were assessed through serum calcium at these stages through 3 cc blood withdrawal. Dietary intake of calcium was also assessed through food frequency charts. Urinary-excretion of calcium was analyzed through cross-linked N-telopeptides (NTx) type I collagen. Each participant was assessed at 3 points including baseline assessment at 1st trimester, then at 2nd trimester and finally at post-partum 4 weeks. At the 2nd trimester ultrasound bone measurement was conducted at distal radius. Quantitative ultrasound was used for this purpose. In the post-partum women, a radiological imaging including DEXA (Dual-energy X-ray absorptiometry) bone scan was performed. Results: The mean age was 26.9±5.5 years. The mean pregnancy was 2.0±1.1 while the mean number of children was 0.9±0.7. The previous months of breast feeding as mean were 6.8±7.9. The calcium intake from food as well as serum calcium levels was below recommended levels in women during their pregnancy and post-delivery. Through the quantitative ultasound and bone density DEXA scan images presented obvious osteoporotic changes in bone density. There were 24% had 2.5 or less meant osteoporosis formation. Conclusion: Women often lead to calcium deficiency during gestation and lactation and thus chances of musculoskeletal disorders escalate manifolds. Radiological imaging can facilitate in detecting these calcium deficiencies. Keywords: Hemostasis, Regulation, Pregnancy, Mineral absorption